2015
DOI: 10.1253/circj.cj-14-1415
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence of the Efficacy of Cell-Based Therapies in Heart Failure

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp diomyocytes or activating endogenous progenitor cells (for review see Behfar et al 8 ). There is enough clinical evidence to conclude that cell therapies are safe. 9-11 However, not all clinical trials show clinical efficacy. Interestingly, cell-based therapy trials are small 9-11 and therefore conclusions drawn from them have limited statistical power. Systematic reviews and meta-analyses are accepted to be robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Peruzzi et al 11 identified 41 trial meta-analyses published by January 2015; of which, 16 involved patients with HF. 11,12 There have been 2 overviews of systematic reviews 11,12 and at least 3 new systematic reviews and meta-analyses published in 2015, notably including an IPD meta-analysis. [13][14][15] Interestingly, Peruzzi et al 11 observed a significant correlation between the A Measurement Score To Assess Systematic Reviews score and the year of publication of these systematic reviews.…”
Section: Systematic Reviews and Trial Meta-analyses Ofmentioning
confidence: 99%
“…Peruzzi et al 11 identified 41 trial meta-analyses published by January 2015; of which, 16 involved patients with HF. 11,12 There have been 2 overviews of systematic reviews 11,12 and at least 3 new systematic reviews and meta-analyses published in 2015, notably including an IPD meta-analysis. [13][14][15] Interestingly, Peruzzi et al 11 observed a significant correlation between the A Measurement Score To Assess Systematic Reviews score and the year of publication of these systematic reviews.…”
Section: Systematic Reviews and Trial Meta-analyses Ofmentioning
confidence: 99%
“…In vitro studies have indicated that MSCs derived from placenta of fetal origin possess greater therapeutic potential compared with MSCs isolated from other tissues and organs [1,2]. Several studies support the ability of these MSCs either to repair or regenerate damaged myocardium [35], although their long-term durability in tissue is controversial [6,7]. The safety of MSC delivery to the left ventricle after acute myocardial infarction has also been established, via intracoronary, intramyocardial, or intravenous routes of administration [8,9].…”
Section: Introductionmentioning
confidence: 99%